2016
DOI: 10.3390/md14120224
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Keratan Sulfate from Shark Cartilage Modulates Gut Microbiota and Increases the Abundance of Lactobacillus spp.

Abstract: Keratan sulfate (KS) represents an important family of glycosaminoglycans that are critical in diverse physiological processes. Recently, accumulating evidence has provided a wealth of information on the bioactivity of KS, which established it as an attractive candidate for drug development. However, although KS has been widely explored, less attention has been given to its effect on gut microbiota. Therefore, given that gut microbiota plays a pivotal role in health homeostasis and disease pathogenesis, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
3
18
0
2
Order By: Relevance
“…This suggests that ECP has a sex-specific effect on gut microbiota. Interestingly, preceding studies have also found similar effects of chondroitin sulfate [ 28 ] and keratan sulfate [ 29 ] on gut microbiota. Given that sex hormones play a critical role in determining the composition of the intestinal microorganisms [ 30 ], our results and past studies [ 28 , 29 ] highlight that dietary fibers may have a gender-specific effect on gut microbiota and clinical therapies using dietary fibers for the treatment of dysbiosis-associated diseases should be tailored according to individuals’ sex.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This suggests that ECP has a sex-specific effect on gut microbiota. Interestingly, preceding studies have also found similar effects of chondroitin sulfate [ 28 ] and keratan sulfate [ 29 ] on gut microbiota. Given that sex hormones play a critical role in determining the composition of the intestinal microorganisms [ 30 ], our results and past studies [ 28 , 29 ] highlight that dietary fibers may have a gender-specific effect on gut microbiota and clinical therapies using dietary fibers for the treatment of dysbiosis-associated diseases should be tailored according to individuals’ sex.…”
Section: Resultsmentioning
confidence: 69%
“…Previous studies indicate that dietary fibers from marine seaweeds with a prebiotic effect could decrease the body weight of experimental mice [ 29 , 56 ]. In accordance with previous reports, ECP, a dietary fiber, was also found to decrease the body weight and energy intake in male and female mice ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of lactobacilli and bifidobacteria to utilize GAGs as carbon sources remains to be determined. Several studies have recently demonstrated that orally administrated Hep, heparosan (precursor of Hep and HS) ( Duan et al, 2013 ), CS-derived oligosaccharides ( Shang et al, 2016b ) and KS ( Shang et al, 2016a ) have potential prebiotic properties, as they were able to modulate the gut microbiota by stimulating the growth of Lactobacillus species. However, an in vitro fermentation model with fucosylated CS and human fecal microbiota resulted in a reduction of Enterobacteriaceae and Lactobacillus cells, while the amounts of Clostridium , Bacteroides, Prevotella , and Bifidobacterium cells increased ( Wei et al, 2017 ).…”
Section: Conjugated Glycans: Glycoproteins and Glycolipidsmentioning
confidence: 99%
“…КС присутствует в центральной нервной системе, обнаружена его функция как регулятора регенерации нейронов. В роговице, по данным сравнительного исследования, содержится в 10 раз больше КС, чем в хряще, и в 2-4 раза больше, чем в какой-либо иной ткани [18][19][20][21][22] (III) Хондроитина 4-сульфат (Х4С)…”
Section: (Ii) кератана сульфатunclassified
“…GlcUAβ1-3'GalNAcβ1-4 Сульфатная группа этерифицирована по 6-му положению -GalNAc(6S) ММ = от 5 × 10 3 до 100 × 10 3 Да Содержится в хрящевых и костных тканях. Х6С преобладает в тканях гидробионтов (до 80 %), ранее его получали из хрящей (плавников) акулы [15,16,[23][24][25][26] (III) ХС D [39] (IV) Гепарин / ГС Антикоагулянт и антитромботическое средство, создает фильтрационный барьер в почках [10] Увеличивает пролиферацию миобластов в присутствии bFGF [39] (II) КС Установлена активность в формировании глиальных рубцов при повреждениях мозга [18], положительная активность в поддержании прозрачности роговицы, пребиотическая активность [9,10,21,22]. В последнее время фармакологическая активность КС интенсивно изучается с целью разрешения его применения в качестве лекарственной субстанции [19,20] (I) ГК Структурообразующий компонент в офтальмологических препаратах и в косметике [40] ХС в животных тканях, как правило, существует в форме протеогликанов.…”
Section: (Ii) кератана сульфатunclassified